Students’ Competency Focuses in Literacy at Language and Letters Faculty, State University of Medan (Unimed), Indonesia - Mara Untung Ritonga (Budapest International Research and Critics University, 2018)
The research aimed at describing Enlgish literacy competency of students, including information literacy. The rational of this research is taken from the vision of Universitas Negeri Medan which is planning to be a world class university. This educational institution which mostly supplies teachers should prepare students the better literacy competency. The first step to develop the competency is to do mapping about English literacy competency of students, including information literacy based on five information literacy standard of Association of College & Research Libraries (ACRL) and The Australian and New Zealeand Institute for Information Literacy (ANZIL). The method used in the mapping is mixed methodology, qualitative and quantitative. The data of the research is 157 students from first and second semester of Indonesian letters Department. The tests done are reading, speaking, listening, speaking and writing, including students competency in accessing and understanding infromation in the internet. The result shows that English/information literacy competency of students vary (60 % low, 30% medium, and 10 % high). There fore, it is necessary to do some efforts to improve English literacy competency of students at the Department of Indonesian Letters Faculty of Language and Arts Universitas Negeri Medan.